Code-Switching in the Instagram Captions of Male and Female Perfume Ads by C&F Store - Matthew Siswanto; Aylanda Hidayati Dwi Nugroho (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This study aims to analyze the types of code-switching used in Instagram captions of male and female perfume advertisements by C&F Store. It focuses on identifying the types used and any differences or similarities between the two. The theory by Hoffmann (2014) divides code-switching into inter-sentential, intra-sentential, and emblematic switching. A total of 40 captions of 20 male and 20 female were manually collected and analyzed using a qualitative approach. Inter-sentential switching appeared 40 times and intra-sentential 39 times; emblematic switching did not appear. No major differences were found between male and female captions, likely due to a shared marketing style or template. This study aims to help readers understand code-switching in Indonesian social media advertising and encourage future research on platforms like TikTok or YouTube.